Individual analysis of EEG background-activity within school age: impact of age and sex within a longitudinal data set - Gmehlin, Dennis; Thomas, Christine; Weisbrod, Matthias; Walther, Stephan; Pfüller, Ute; Resch, Franz; Oelkers-Ax, Rieke (International journal of developmental neuroscience, 2011)
Objectives Quantitative EEG can monitor changes in brain function during development and may help to understand developmental disorders. However, current EEG-databases are primarily based on standardized frequency bands which disregard age-related changes in alpha peak frequency (PF) and therefore complicate the interpretation of spectral estimates in the theta and alpha range. Methods We used a two point longitudinal design in order to analyze intraindividual changes in 40 healthy children and adolescents with age (T1: 6-18 years; interval approximately 4 years). Using a 64-channel eyes closed resting EEG we calculated absolute/relative power in individualized frequency bands (IFB: delta, theta, alpha1/2 and beta) based on PF. Results PF increased with age, with changes being larger for children than adolescents. Controlling for changes in PF, changes in absolute/relative alpha1/2 power and in absolute beta power were minor. Relative beta power, however, increased while absolute/relative delta and theta power decreased massively. Sex-differences in PF did not reach significance. However, boys exhibited larger changes during adolescence than girls for all absolute power measures except alpha. Conclusion Normal EEG development during school-age is mainly based on an absolute decrease of slow frequency activity and increases of PF which may be interpreted in terms of a reorganization of the EEG towards a higher frequency oscillatory scale rather than a maturation of the theta-alpha1/2 band power sequence. Age-related changes differed between boys and girls suggesting a different developmental timing for the sexes. In future studies a combined analysis of PF and IFB may help to specify deviations in developmental disorders.
First published: 04 December 2010
Gesehen am 27.06.2022